A Ludicidade em turma de séries iniciais: uma análise das práticas pedagógicas em uma escola no meio rural do município de Breves-Marajó-PA - ALVES, Rosinete Viana (2019)
The present work seeks in the ludic a response to the application of teaching learning with elementary school students in a rural school in the municipality of Breves, where the logic is to show based on a research conducted in a group with this profile, how this works the playful and can change the focus of education in this place. For the basis of this analysis we have an interview with the teacher regent and on top of this we seek to analyze his practical works. We searched for theoretical underpinnings in KISHIMOTO, T. M .; PIAGET, J.A .; TUBINO, L.B. among others. For the research we use the qualitative method. The theme of the ludic presented here does not have an aspect for the entertainment or hobby, but as a point of reference for the student to enter the theme, for this is sought to show the way the teacher works and his attitude towards diversity of application that the games and the games provide both for the students to feel involved, so that the latter can understand the content itself without having to do it in a mechanized way, for this, it is based on a script that goes from the interview with the teacher to the way he works the playful relation to the curricular activities.